The language biography in the socio-political process. The example of Polish woman form the Republic of Moldova - Krasowska, Helena (Balcanica Posnaniensia. Acta et studia, 2022)
The language biography in the socio-political process: The example of Polish woman from the Republic of Moldova. The aim of this article is to show what sociolinguistic factors influence the shaping of an individual’s multilingualism and what is the correlation between the languages used in the historical and social context. Factors influencing the multilingualism of an individual depend on the place of birth (father’s language, mother’s language), place of residence (village, city, number of speakers in a given language), the status and prestige of the language (the language of the state administration, the language of a minority group), the state’s language policy (constant, variable). The socio-political situation of the Republic of Moldova was outlined in order to understand the specific linguistic case of Poland living in Chisinau and her life in languages, and to show the role of an individual’s language in the context of socio-political changes in Moldova. Various social, political and economic factors influenced the multilingualism of the Polish woman from Chisinau. Over the course of her long life, the range of language use and the competences in each of them have changed. External factors shaped her linguistic behavior. Political and social events in this part of Europe influenced the change, use and acquisition of new languages.